Lignocellulosic jute fiber as a bioadsorbent for the removal of azo dye from its aqueous solution: Batch and column studies. Issue 1 (18th July 2012) - Roy, Aparna; Chakraborty, Sumit; Kundu, Sarada Prasad; Adhikari, Basudam; Majumder, Subhasish Basu
Abstract The feasibility of the use of jute fiber for the adsorption of azo dye from an aqueous solution was evaluated with batch and fixed‐bed column studies. The batch studies illustrated that dye uptake was highly dependent on different process variables, namely, the pH, initial dye concentration of the solution, adsorbent dosage, contact time, ionic strength, and temperature. The exothermic and spontaneous nature of adsorption was revealed from thermodynamic study. The equilibrium adsorption data were highly consistent with the Langmuir isotherm and yielded an R2 value of 0.999. Kinetic studies divulged that the adsorption followed a pseudo‐second‐order model with regard to the intraparticle diffusion. In the column studies, the total amount of adsorbed dye and the adsorption capacity decreased with increasing flow rate and increased with increasing bed height and initial dye concentration. Also, the breakthrough time and exhaustion time increased with increasing bed depth but decreased with increasing flow rate and influent dye concentration. The column performances were predicted by the application of the bed‐depth service time model and Thomas model to the experimental data. The virgin and dye‐adsorbed jute fiber was characterized by Fourier transform infrared spectroscopy and scanning electron microscopy analyses. The investigation suggested that jute fiber could be applied as a promising low‐cost adsorbent for dye removal. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013